FORMULASI SEDIAAN SABUN MANDI PADAT EKSTRAK ETANOL UBI JALAR UNGU (Ipomea batatas L) SEBAGAI PELEMBAB KULIT - Suci Wulandari; Ayu Renta Niasari Silaen; Nur Ulina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Soap is a surfactant used to clean or wash something that is available in solid and liquid form. Soap can be useful as a cleaning tool, this is because soap molecules contain polar (bonded with water) and non-polar (bonded with oil) groups so that they can clean grease or dirt that is not lifted by water. Purple sweet potato (Ipomoea babatas L) is a sweet potato that has natural dyes as anthocyanins that function as antioxidants. The purpose of this study was to obtain a solid bath soap formulation with purple sweet potato extract (Ipomoea batatas L). Furthermore, purple sweet potato extract was formulated based on a formula with a concentration difference of 3.5%, 4.5%, 5.5%. Furthermore, the preparations that have been made are carried out by organoleptic tests, pH tests, and foam stability tests. It can be concluded that purple sweet potato extract can be used as a solid soap preparation and there is an effect of concentration on the quality of the organoleptic test soap, pH, foam stability and moisture content.